Compendio nacional de estadísticas de recursos hídricos 2017 - Autoridad Nacional del Agua (2018)
Equipo Técnico: William Robert Atencio Mamani, Jean Carlo Céspedes Reátegui, Litzia Nidia Cisneros, Huamaní, Lucy Julca De La Cruz, Juan Pablo Mariluz Silva, Benjamín Roisy Molina Chávez, Silvia Sachiko Ramos Tamayo, Luz Áyde Carrillo Moscoso; Edwin Zenteno Tupino, Dalila Zulema Navarro Ruíz, Gustavo Adolfo Palomares Córdova, Christian De La Torre Mayta, Víctor Antonio Huapaya Avalos, Víctor David Godoy Jiménez, Homero Roosevelt Guerrero Aranda, Alex Favio Paco Narváez, Luis Alberto Torres Obando, Carlos Morales Pingo, Gloria Soledad Aguilar Rivera, Sandro Miguel Rosales Vargas, César Luque del Carpio, Jessenia Cárdenas Campana.